Handbook of Erosion Modelling 2010
DOI: 10.1002/9781444328455.ch11
|View full text |Cite
|
Sign up to set email alerts
|

Use of GUEST Technology to Parameterize a Physically‐Based Model for Assessing Soil Erodibility and Evaluating Conservation Practices in Tropical Steeplands

Abstract: Probably the largest body of data on soil erosion has been that collected using the USLE methodology, thus lacking measurement of runoff rates. In the ASIALAND section of this chapter it is demonstrated that the GUEST methodology can be applied to data collected for analysis using the USLE methodology. Thus there is the opportunity, in future, to analyse other USLE data sets to yield values of β which would be expected to provide further evidence of how soil erodibility is affected by soil characteristics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…The decreasing trend in the parameter F as the stream power increases is in contrast with experimental observations of Proffitt et al (1993). Proffitt et al (1993) conclude that a constant value of 0.1 is appropriate for the fraction of the stream power expended in maintaining sediments in suspension, and this constant value has been subsequently used for field applications and experimental study of multiclass sediment deposition with flow impoundment as a result of vegetation buffer strips (Rose et al 2011;Hussein et al 2007). By comparison with this set of experiments considered in the paper, the flow condition used by Proffitt et al (1993) was much weaker and sediment concentration much smaller.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The decreasing trend in the parameter F as the stream power increases is in contrast with experimental observations of Proffitt et al (1993). Proffitt et al (1993) conclude that a constant value of 0.1 is appropriate for the fraction of the stream power expended in maintaining sediments in suspension, and this constant value has been subsequently used for field applications and experimental study of multiclass sediment deposition with flow impoundment as a result of vegetation buffer strips (Rose et al 2011;Hussein et al 2007). By comparison with this set of experiments considered in the paper, the flow condition used by Proffitt et al (1993) was much weaker and sediment concentration much smaller.…”
Section: Discussionmentioning
confidence: 82%
“…While material of this caliber is not typical of sediments carried by overland flows, Yalin's formula is implemented in WEPP because the formula performed favorably in comparison with several other formulas (Alonso et al 1981). For Griffith University Erosion System Template (GUEST), the sediment transport capacity is seen as a result of dynamic balance of simultaneous erosion and deposition processes (Hairsine and Rose 1992a;Misra and Rose 1996;Rose et al 2011). The conceptual basis for this approach can be traced back to Bagnold who assumed that a fraction of stream power would be expended on sediment transport (Bagnold 1966;Rose et al 1983a, b).…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of this infiltration equation, and its preference as a method of choice over the use of alternative infiltration models has been well established in multi‐country studies at runoff plot scale (Yu et al ., , ; Yu and Rose, ; Rose et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…In soil erosion, soil conservation and agricultural contexts, where experimental and field studies are generally concerned with shallower overland flows, other streams of literature have developed with a focus on physical process description (e.g. Hairsine and Rose, , ; Proffitt et al ., ; Misra and Rose, , ; Nearing et al ., ; Ciesiolka et al ., , ; Yu et al ., ; Fentie et al ., ; Sander et al ., , : Yu and Rose, ; Presbitero et al ., ; Rose et al ., , ; Armstrong et al ., ). This line of research has demonstrated the distinct advantages of the modelling approach of Hairsine and Rose (, ) in which multiple classes of settling velocity rather than particle size are used, and a distinction is made between the entrainment by flow of original soil profile material, or soil matrix, and the re‐entrainment of recently deposited material which is much weaker, and may offer negligible resistance to erosive processes.…”
Section: Introductionmentioning
confidence: 99%
“…Values of F as large as ≈ 0.1 have been determined in shallow overland flows (e.g. Proffitt et al ., ; Yu et al ., ; Rose et al ., ). In contrast Bagnold () found values of about 0.015 for a similar factor with total suspended sediment in rivers.…”
Section: Discussionmentioning
confidence: 97%